Migration and Islamic ethics : issues of residence, naturalization and citizenship - Jureidini, Ray; Hassan, Said Fares (Studies in Islamic ethics, 2020)
"Migration and Islamic Ethics, Issues of Residence, Naturalization and Citizenship addresses how Islamic ethical and legal traditions can contribute to current global debates on migration and displacement; how Islamic ethics of muʼakha, ḍiyāfa, ijāra, amān, jiwār, sutra, kafāla, among others, may provide common ethical grounds for a new paradigm of social and political virtues applicable to all humanity, not only Muslims. The present volume more broadly defines the Islamic tradition to cover not only theology but also to encompass ethics, customs and social norms, as well as modern political, humanitarian and rights discourses. The first section addresses theorizations and conceptualizations using contemporary Islamic examples, mainly in the treatment of asylum-seekers and refugees; the second, contains empirical analyses of contemporary case studies; the third provides historical accounts of Muslim migratory experiences"--